Investigating the effect of inbound tourism on FDI: The importance of quantile estimations - Arain, Hira; Han, Liyan; Sharif, Arshian; Meo, Muhammad Saeed (Sage Journal, 2019)
The current study investigates the asymmetric effect of inbound tourism on foreign direct investment (FDI) in the world’s top tourist destinations based on monthly data for the period between 1995 and 2017. The quantile-on-quantile (QQ) approach introduced by Sim and Zhou was adopted for this study, because it assesses how various quantiles of inbound tourism affect different quantiles of FDI. Thus, the QQ approach gives a more detailed explanation of the general dependence of inbound tourism and FDI than traditional approaches, such as ordinary least squares or quantile regression. Further, the test of Granger causality in quantiles proposed by Troster et al. was also applied in this study to check the causal relationship between inbound tourism and FDI. The empirical outcomes explain that the relationship between inbound tourism and FDI is mostly positive for all countries except Mexico and Russia on low and middle quantiles, although there are significant differences throughout the nations and across all quantiles of inbound tourism and FDI.